Exploring microfluidics as a tool to evaluate the biological properties of a titanium alloy under dynamic conditions. (6th October 2020) - Carter, Sarah-Sophia D.; Barbe, Laurent; Tenje, Maria; Mestres, Gemma
Abstract : When evaluating the biological properties of titanium under dynamic conditions, cell proliferation was shown to be dominant over cell differentiation. Abstract : To bring novel biomaterials to clinical use, reliable in vitro models are imperative. The aim of this work was to develop a microfluidic tool to evaluate the biological properties of biomaterials for bone repair. Two approaches to embed medical grade titanium (Ti6 Al4 V) on-chip were explored. The first approach consisted of a polydimethylsiloxane microfluidic channel placed onto a titanium disc, held together by an additively manufactured fixture. In the second approach, a titanium disc was assembled onto a microscopic glass slide, using a double-sided tape microfluidic channel. Both approaches demonstrated potential for maintaining MC3T3-E1 preosteoblast-like cell cultures on-chip, as was shown by the vast majority of living cells after 1 day. In addition, the cells cultured on-chip showed a more elongated morphology compared to cells grown under static conditions and a tendency to align to the direction of the flow. For longer-term ( i.e. 10 days) studies, the glass-based chip was selected. Assessment of cell viability showed a high number of living cells during the entire experimental period. Cell proliferation and differentiation studies revealed an increase in cell proliferation on-chip, suggesting that proliferation was the dominating process at the detriment of differentiation in this micrometric dynamic environment. These results illustrate the importance of optimizing in vitro cell culture conditions and how these may affect biomaterial testing outcomes. Overall, this work provides a step towards more in vivo -like microfluidic testing platforms, which are expected to provide more reliable in vitro screening of biomaterials.